Acetaldehyde Induces an Endothelium-Dependent Relaxation of Superior Mesenteric Artery: Potential Role in Postprandial Hyperemia - Jin, Lexiao; Lorkiewicz, Pawel; Malovichko, Marina V.; Bhatnagar, Aruni; Srivastava, Sanjay; Conklin, Daniel J. (Frontiers in Physiology, 2019)
Acetaldehyde (AA) is a small, ubiquitous compound present in foods, beverages, as a gas phase combustion product, and also endogenously generated from metabolism as from ethanol (EtOH). Acetate is a short chain fatty acid derived from AA oxidation, and acetate levels were significantly higher in urine collected overnight with food provided ad libitum compared with urine collected after 9 h fasting. Feeding increases gastrointestinal blood flow, and thus, we explored the direct effects of AA (and acetate) in isolated murine superior mesenteric artery (SMA). Over the concentration range of 1–100 mM, AA strongly, and reversibly relaxed agonist-induced contractions of SMA including phenylephrine (PE), thromboxane A2 analog (U46,619) and high potassium (High K+) without toxicity. The sensitivity (EC50) but not the efficacy (>90% relaxation of PE-precontraction) of AA-induced relaxations was dependent on blood vessel (SMA was 3× more sensitive than aorta) and contractile agonist (PE EC50 = 3.3 ± 0.4 mM; U46,619 EC50 = 14.9 ± 1.5 mM; and High K+ EC50 = 17.7 ± 0.5 mM) yet independent of circadian cycle and sex. The most sensitive component of the AA-induced relaxation was inhibited significantly by: (1) a mechanically impaired endothelium; (2) nitric oxide synthase (NOS) inhibitor (L-NAME); and (3) a guanylyl cyclase (GC) inhibitor (ODQ). Both acetate and EtOH stimulated much weaker relaxations in SMA than did AA, yet these relaxations were significantly inhibited by L-NAME as well. Neither EtOH nor acetate relaxed pre-contracted aorta. Although neither cyanamide, a non-specific aldehyde dehydrogenase (ALDH) enzyme inhibitor, nor Alda-1, a specific activator of ALDH2 activity, had any effect on either sensitivity or efficacy of AA-induced relaxation in SMA, cyanamide significantly blocked both EtOH- and acetate-induced relaxations in SMA implicating a role of ALDH activity in vasorelaxation. These data show that AA relaxes SMA via an endothelium- and NO-dependent mechanism indicating that AA may be one component of the complex post-prandial hyperemia reflex via vasodilatation of mesenteric vasculature.